Characterization of Pulling Forces Exerted by Primary School Children While Carrying Trolley Bags. (September 2013) - Pau, Massimiliano; Leban, Bruno; Paderi, Maurizio; Nussbaum, Maury A.
Carriage of school items by children remains an issue of concern, mainly due to the large loads they have to bear, starting from early age when the musculoskeletal structure is still under development. As such, children are potentially exposed to important risks of acute or chronic injuries due to such carriage. While backpack remains the most common modality, in recent years trolley bags are increasingly considered and used. Trolleys may be of benefit, as much of the load can supported by the ground, and the muscular effort is limited to a pulling force. Nevertheless, there are situations (like stair ascent and descent, steps, and ramps) where the pulling force increases or, in some cases, has to be fully supported by a single arm. Under such conditions, the use of trolley bag might be disadvantageous versus a backpack, in that the latter allows a symmetrical distribution of the load on the body in a range of conditions. To provide more empirical evidence, which at present is very limited, this study aimed to characterize the pulling forces needed when using a school trolley bag, on a route that includes level and inclined ground surface, steps, and stairs. A sample of 195 students of primary school (age 8-11) participated, and they were asked to pull an instrumented trolley loaded with school items (total load = 62 N) from the school entrance to a classroom located one floor up in the school building. The results, expressed in terms of "pulling force vs. time" curves, show that particularly during stairs ascent and descent, one arm may exert quite large dynamic forces, and that these forces can be up to twice the mass of the carried load. Although exposure to such loads is quite limited, the methodology described here highlights the potential for concern and provides a basis for future investigations of the contribution of trolley bag carriage and disorders of the arm-shoulder complex among children.